The effects of rifaximin and lactulose on the gut-liver-brain axis in rats with minimal hepatic encephalopathy - Xueyan Lin; Zhengchao Zhang; Yi Lin; Shiyun Lu; Rongrong Chen (PLoS ONE, 2025)
Background The principal therapeutic agents for minimal hepatic encephalopathy (MHE), which focus on the modulation of the gut microbiota, include lactulose and rifaximin; however, the precise mechanisms through which they operate remain unclear. Aim This study aimed to investigate the effects of rifaximin and lactulose on the gut-liver-brain axis in a rat model of MHE and to clarify the underlying mechanisms involved. Methods A rat model of MHE was established by subcutaneous carbon tetrachloride (CCl4) injection. The Morris water maze (MWM) test was used to assess cognitive function in MHE rats following treatment with rifaximin and lactulose. Serum and cerebrospinal fluid ammonia levels were quantified, along with measurements of portal lipopolysaccharide (LPS) and various serum inflammatory markers. Furthermore, the expression of Toll-like receptor 4 (TLR4) in the liver was examined by histopathological evaluation. Additional analyses included the detection of tight junction proteins in the intestinal mucosa as well as colon fecal 16S rRNA sequencing and metabolic pathway assessments. Results Both rifaximin and lactulose were effective in reducing ammonia concentrations in MHE rats and ameliorating cognitive deficits, although they exhibited a minimal impact on hepatic function. Post-treatment assessments revealed significant reductions in portal LPS, serum interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). The expression of TLR4 in the liver and hepatic inflammatory infiltration were notably diminished. Rifaximin administration led to increased occludin expression in the intestinal tissues of MHE rats. Despite no significant alterations in the diversity or composition of the gut microbiota, metabolic pathway analyses indicated a downregulation of glycometabolism pathways following treatment. Conclusion Rifaximin and lactulose may enhance cognitive performance in MHE rats by modulating gut microbiota metabolism and preserving the intestinal barrier integrity. This modulation is associated with lowered ammonia levels, decreased translocation of LPS to the liver, and reduced inflammatory response, both in the liver and systemically.